Homocysteine levels are independently associated with damage accrual in systemic lupus erythematosus patients from a Latin-American cohort - Zeña-Huancas, Paola A. (2018)
Objective: To determine the impact of homocysteine levels on damage accrual in systemic lupus erythematosus (SLE) patients. Methods: This longitudinal study was conducted in consecutive patients seen every 6 months at our Rheumatology Department since 2012. Patients with available homocysteine levels and who had at least one subsequent visit were included. Univariable and multivariable Cox regression models were done to determine if homocysteine levels were predictive of damage accrual as per the SLICC Damage Index (SDI). The multivariable model was adjusted for pertinent variables (age at diagnosis, gender, socioeconomic status, disease duration, disease activity (SLEDAI), Framingham score, antimalarial and immunosuppressive drug use, average daily dose, and exposure time to prednisone (PDN)). Results: One hundred forty-five patients were included; their mean (SD) age at diagnosis was 43.70 (12.09) years, 136 (93.8%) were female, and nearly all were Mestizo. At baseline, disease duration was 7.55 (6.73) years; patients were followed for 3.54 (1.27) years. The SLEDAI was 5.60 (4.34), and the SDI 0.97 (1.35). The average daily PDN dose was 7.30 (5.78) mg/day and the time of PDN exposure was 7.36 (6.73) years. Mean homocysteine levels were 10.07 (3.71) μmol/L. The highest tertile of homocysteine levels predicted new damage accrual in the univariable and multivariable models [HR 1.78 (95% CI, 1.042–3.039); p = 0.035 and HR 2.045 (95% CI, 1.077–3.883); p = 0.029, respectively]. Increased levels (> 15 μmol/L) were found in 12 (8.3%) patients; 75 (51.7%) patients increased ≥ 1 SDI point. Conclusion: In SLE patients, homocysteine levels predicted damage accrual independently of other well-known risk factors for such occurrence. © 2018, International League of Associations for Rheumatology (ILAR).